Respostas

2013-04-16T10:28:28-03:00

Bom dia, olha, é só vocÊ  substituir x por 5 e y por -1 na expressão. 

 

(5)² = 5 . 5 = 25 

 

- com - = + --> por isso, - 30 vezes  -1 = 30 

 

 

x²-6xy

(5)² - 6 . 5 . (-1) = 

25 - 30 . (-1) = 

25 - (-30) = 

25 + 30 =

55 --> resposta. .

1 5 1
2013-04-16T10:28:59-03:00

x²-6xy,para x=5 e y= -1

 

é so substiuir os valores.

 

5²-6*5*(-1)    explicação ( 5² = 5*5 = 25)

25+30            explicação -6 +5*-1 =- 6 -5 = + 30 

55

 

Solução 55

1 5 1